Factors That Determine the Adoption Intention of Mobile Chatbots for Customer Service: An Empirical Study from Greece - Paraskevi GATZIOUFA; SAPRIKIS Vaggelis; ANTONIADIS Ioannis (Communications of International Proceedings, 2023)
Technological advances have considerably contributed to creating effective communication between businesses and customers. Based on Artificial Intelligence (AI), chatbots, which are text- or voice-based virtual assistants, promote customer interaction and service at any time, and are particularly popular among young people, who constantly use smartphones for numerous transactions and communication. The present research was carried out with a view to investigating the factors encouraging the use and adoption of artificial intelligence agents by people who have not used them in digital contexts. Given that the relevant research in the specific target group is rather poor, the work attracts particular interest. The present paper, based on the UTAUT 2 model, investigates the factors affecting the intention to adopt chatbots of 411 University students in Greece. For the purpose of the research, electronic questionnaires were used, which were distributed to the participants via Google Forms. Data analysis was based on factor analysis and stepwise regression analysis. The research results demonstrated that the sample is affected by five factors established by the statistical analysis of the collected data, namely, performance expectancy, social influence, facilitating factors, hedonic motivation, and trust. However, two factors, effort expectancy and anxiety, were not found to fit the model. The research yielded valuable results, which should be seriously considered by businesses in their effort to develop chatbot strategy and design, aimed at effective communication with their customers, especially young people.
Keywords: chatbots; UTAUT; text-bots; adoption intention